Plant domestication - Vaughan, Duncan (Henry Stewart Talks, 2014)
Domestication, cultivation, evolution and co-evolution, Centers of crop origin and centers of crop diversity, Wild plant characteristics verses domesticated plant characteristics, The domestication syndrome, bottle neck of domestication, selective sweeps, Mutation, polyploidy, translocation, duplication and retro-transposons, Ex-situ, In-situ and On-farm conservation